2019
DOI: 10.1177/0898010119887595
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Care Perceptions of Baccalaureate Nursing Students

Abstract: Purpose: The purpose of this study was to examine baccalaureate nursing (BSN) students’ perception of spirituality and spiritual care as a component of holistic nursing practice. Aim: The specific aim of this study was to determine the perception levels of spiritual care, religiosity, and spirituality in first- and last-semester BSN students. Method: This descriptive cross-sectional study used a convenience sample of BSN students. Participants ( n = 150) completed demographics with self-reflected levels of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…In this study, the total score of spiritual care perceptions was 173.83 ± 25.62, which was quite moderate and similar to the results of Hu et al (2019) and Pipkins et al (2020), and it also needs to be further improved. Besides, the total score of spiritual well-being was 98.74 ± 12.87, which was also quite moderate and consistent with the results of Hsiao et al (2013).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the total score of spiritual care perceptions was 173.83 ± 25.62, which was quite moderate and similar to the results of Hu et al (2019) and Pipkins et al (2020), and it also needs to be further improved. Besides, the total score of spiritual well-being was 98.74 ± 12.87, which was also quite moderate and consistent with the results of Hsiao et al (2013).…”
Section: Discussionsupporting
confidence: 88%
“…Different results were reported in the literature. In addition to studies (Aslan & Ünsal, 2021; Ovayolu et al, 2021; Pipkins et al, 2020) stating that SSCRS score was higher in fourth grades, Abbasi et al (2014) found no difference between first and fourth grades in their study. It is thought that this difference in studies is due to regional differences.…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, Galloway and Hand's (2017) study identified nursing students’ knowledge in spiritual care competencies and self-awareness increased after participating in a spirituality course. Pipkins et al (2020) integrated spirituality content throughout the nursing program and noted final semester students’ perceptions of their spiritual care knowledge increased.…”
mentioning
confidence: 99%
“…Nursing research suggests it is essential to teach undergraduate nursing students the importance of spirituality and spiritual care (Azarsa et al, 2015; Pipkins et al, 2020). However, little is known if students’ reported personal spirituality and perceived ability to provide spiritual care contributes positively or negatively in their actual provision of spiritual care.…”
mentioning
confidence: 99%